The role of participatory approach in reducing social vulnerability : the example of a social intervention aiming at the re-housing of families belonging to a marginalized Roma community - Olimpiu Bela Lacatus; Júlia Adorjáni; Ágnes David-Kacsó; Imola Antal; Gabriella Tonk (Revista română de economie, 2017)
The paper explores the issue of how social interventions in deeply marginalized communities should be conceived in order to prevent further victimization of the most vulnerable groups within the community: children and women. The analysis relies on the example of a pilot project, which is implemented in one of the most marginalized and stigmatized Roma communities in Romania. Within the housing component of the pilot project, participatory social housing will be piloted in the context of coordinated intervention. 32 apartments outside the marginalized area will be built/purchased, destined exclusively to the marginalized communities in case. Since the number of housing units achieved within the project represents only approximately 10% of the total amount of housing units needed for the spatial desegregation of the communities living at present in the marginalized area, we face the issue of having to select those families, which could benefit from these apartments. At present, the Romanian public and private system of social assistance is not capable of ensuring the necessary support, either in terms of social services or in terms of financial support, in order to surpass complex situations of vulnerability of families living in marginalized communities. Therefore, even if the project promotes the principle of the right to housing, the methodology fits into a housing ready policy. Without the intention to reward those who have more resources at their disposal, we needed to create an accession system, which is at the same time a complex system for assessing the needs and resources of the families filing for a social apartment. The project methodology adopts the perspective of rights, with express emphasis on children?s rights, and a systemic approach, which takes into account various levels of intervention. The paper presents and analyzes the participatory methodology used to create the accession system for the social housing. For this, we adopt the critical perspective, the model of structuralism and the notion of structural violence? in order to explain the interconnectedness of the community dynamics and institutional mechanisms that enhance vulnerability instead of reducing it. The participatory approach overarched the different phases of the intervention on both community and institutional level: the assessment of housing needs, the assessment of needs before and after moving to the social houses, and the development of eligibility and evaluation criteria. The paper advocates the participatory approach allowing the counterbalancing of power relationships not just between the community and the institutions, but also inside the community, thus attempting to protect the most vulnerable members of the community. The paper also reflects on the difficulties and limits of the participatory approach, and raises awareness on the institutional responsibility when creating the context and reality of participation.
2665773-9; 2344-4657; Revista română de economie; 717197875